(untitled) (Experimental biology, 2015)
The discovery of induced pluripotent stem cells in 2006 opened new capabilities for the use of stem cells in regenerative medicine, research of ageing mechanisms, pathogenesis of genetic disorders and clinical drug trials. However, there are substantial drawbacks for the use of induced pluripotent stem cells in medicine and pharmacology. In this review we discussed advantages and limitations of this technology in regards to regenerative medicine, pathogenesis of genetic conditions and clinical drug trials.